Being Accepted or Ostracized: How Social Experience Influences Consumer Responses to Advertisements with Different Regulatory Focus. Issue 3 (26th May 2020) - Wu, Linwan; Dodoo, Naa Amponsah
Abstract : Social experience (i.e., social inclusion versus exclusion) is an important factor that influences consumer behaviors but has not been adequately examined in advertising research. To fill this gap, we conducted three experiments to investigate how consumers' social experiences affect their responses to promotion-focused versus prevention-focused advertisements. Our findings indicated that consumers who experienced being included or being ignored responded more favorably to promotion-focused advertisements than prevention-focused advertisements. However, these effects were due to different underlying mechanisms. Consumers who experienced being rejected were indifferent to advertisements' regulatory focus, but they preferred promotion-focused advertisements once they received a self-esteem boost. These findings are believed to provide meaningful contributions to both advertising research and practice.